Fast and high temperature hyperthermia coupled with radiotherapy as a possible new treatment for glioblastoma. Issue 1 (December 2016) - Borasi, Giovanni; Nahum, Alan; Paulides, Margarethus; Powathil, Gibin; Russo, Giorgio; Fariselli, Laura; Lamia, Debora; Cirincione, Roberta; Forte, Giusi; Borrazzo, Cristian; Caccia, Barbara; di Castro, Elisabetta; et al.
Abstract Background A new transcranial focused ultrasound device has been developed that can induce hyperthermia in a large tissue volume. The purpose of this work is to investigate theoretically how glioblastoma multiforme (GBM) can be effectively treated by combining the fast hyperthermia generated by this focused ultrasound device with external beam radiotherapy. Methods/Design To investigate the effect of tumor growth, we have developed a mathematical description of GBM proliferation and diffusion in the context of reaction–diffusion theory. In addition, we have formulated equations describing the impact of radiotherapy and heat on GBM in the reaction–diffusion equation, including tumor regrowth by stem cells. This formulation has been used to predict the effectiveness of the combination treatment for a realistic focused ultrasound heating scenario. Our results show that patient survival could be significantly improved by this combined treatment modality. Discussion High priority should be given to experiments to validate the therapeutic benefit predicted by our model.